Inhibition of cystathionine-γ-lyase-mediated hydrogen sulfide production in LPS-stimulated RAW 264.7 macrophages by polyherbal extract (Indian Journal of Experimental Biology (IJEB), 2021)
The polyherbal formulation chandraprabha vati (CV) comprising 29 herbs is traditionally used as an anti-inflammatory agent for arthritis and urinary ailments in Indian Siddha medicine. Earlier, we reported that lipopolysaccharide (LPS) induced apoptosis in RAW 264.7 macrophages is mediated by hydrogen sulfide (H2S), a potential target for many inflammatory diseases. Here, we hypothesized that pretreatment with CV decreases H2S level and thereby alleviate the inflammatory conditions induced by LPS in RAW 264.7 macrophages, and this protective effect occurs through alterations in cystathionine-γ-lyase (CSE), a H2S synthesizing enzyme. Accordingly, we evaluated the anti-inflammatory effect of CV in LPS-stimulated RAW 264.7 macrophages in vitro. The CV pretreatment followed by 12 h of LPS-stimulation showed significantly decreased TNF-α, H2S production possibly through CSE gene expression and NF-кB activation compared to the non pretreated macrophages. Our results further confirm that the polyherbal extract chandraprabha vati may be a useful therapy for inflammatory disorders by reducing H2S levels.